Conducted EMI mitigation in transformerless PV inverters based on intrinsic MOSFET parameters. (November 2020) - Kraiem, S.; Hamouda, M.; Slama, J. Ben Hadj
Abstract: Electromagnetic interferences (EMI) caused by the high switching frequency of power semiconductors in transformerless single-phase grid-connected photovoltaic (PV) inverters have adverse effects on the lifetime of PV cells and reliability of the electronic and domestic equipment in the neighborhood of the PV installation. This paper proposes a design methodology that helps electronic circuit designers reduce EMI in single-phase PV inverters involving a large number of power semiconductors. Firstly, the most disturbing sources (switching cells) in terms of EMI are identified. Thereafter, a careful choice of the Si-MOSFET assigned to these sources is performed based on its intrinsic parameters. The method is applied to an H5 PV inverter and validated with numerical simulations and experimental tests. The obtained results show a decrease in the conducted EMI after the identification of the disturbing source and the selection of the Si-MOSFET with appropriate intrinsic parameters.